Danolestes moelleri gen. et sp. nov., the first lestoid (Zygoptera: Odonata) from the early Ypresian Fur Formation of Denmark shows faunistic affinity to South America - Simonsen, Thomas J.; Archibald, S. Bruce; Rasmussen, Jan A.; Sylvestersen, René L.; Olsen, Kent; Ware, Jessica L. (Zootaxa, 2025)
We describe Danolestes moelleri gen. et sp. nov., the first spreadwing damselfly (Odonata, Zygoptera, Lestoidea) known from the Danish earliest Eocene Fur Formation. The new taxon is placed in Lestoidea, and tentatively affiliated with Priscalestes and Promegalestes, two extinct genera known from Western Palearctic and South America respectively, highlighting the complex biogeographical affiliations of the Fur Formation biota. D. moelleri gen. et sp. nov. was preserved in a ‘striated concretion’ block from the Paleocene-Eocene Thermal Maximum (PETM) recovery phase. It is the second odonate and first zygopteran described from the PETM recovery phase of the Fur Formation.